2018
DOI: 10.1080/10963758.2018.1437350
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Alumni’s Intention to Engage in Nonmonetary Activities: A Cross-Generational Comparison Study

Abstract: A growing supporting and involving alumni group is one of the critical components of a quality hospitality management program. Universities increasingly count on their alumni to make monetary and non-monetary contributions. Yet, different generational alumni's intentions to make non-monetary contributions, such as participating in activities and social events, have not been thoroughly examined. Through an online alumni survey (N = 566, response rate 7%), this research identified different generational alumni's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Alumni preference to engage in nonmonetary support highlighted the limited capacities of alumni, which is consistent with some recent studies. For example, Chen (2018) highlighted this unique aspect while researching European alumni and reported that alumni prefer to engage in nonmonetary activities rather than monetary activities with institutions. However, alumni perception of nonmonetary engagement as indirect monetary support to PHEIs has presented a unique aspect of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Alumni preference to engage in nonmonetary support highlighted the limited capacities of alumni, which is consistent with some recent studies. For example, Chen (2018) highlighted this unique aspect while researching European alumni and reported that alumni prefer to engage in nonmonetary activities rather than monetary activities with institutions. However, alumni perception of nonmonetary engagement as indirect monetary support to PHEIs has presented a unique aspect of this study.…”
Section: Discussionmentioning
confidence: 99%